Relação família e escola: a importância da participação da família na vida escolar do aluno - SANTOS, Edilma Silva (2021)
This work is the result of a research entitled "Family and School Relationship: The importance of family participation in the student's school life", taking into account the family / school relationship within the municipality of Anapu - Pará, aiming to demonstrate that family / school relationship has been presented. In order to do so, field research was carried out in 06 elementary schools at the county seat in order to gather information that could lead us to the conclusions presented at the end. It should be emphasized that this study had as subjects the pedagogical coordinators, teachers and parents of students. The data were collected through questionnaires followed by interviews, analyzed in the light of theorists who deal with the subject. After tabulation of the data collected, they were presented in tables for a better understanding. Thus this research assumes a quantitative approach to descriptive objects subsidized by bibliographic research. In this way, it was verified that family and school are the two main institutions in the construction and formation of the subjects, being, therefore, the partnership between them necessary to the process of teaching and learning of the student. Research has also shown that there is no family / school exchange, in addition to parent-teacher conferences. It was verified that the work has been the main obstacle to the process of family participation in the school space, it was also possible to perceive that there are no school programs that encourage this partnership.